THE PREFERENCES FOR HOUSING LOAN DEMAND IN INDONESIA BEFORE AND AFTER THE LOAN-TO-VALUE POLICY CHANGE - Ayuningtyas, Fitri Juniwati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The high price of houses causes a person to not be able to buy a home. The way that someone can own a house is by taking advantage of the credit offers provided by the bank. A mcroprudential policy needed that aims to overcome financial system instability, one of which is the policy on easing the loan-to-value (LTV) ratio for housing loans (KPR). The adjustment of LTV ratio aims to increase the potential demand for property, especially housing and household appliances, in line with an increase in the incomes of the lower middle class, and to control risks in the property sector. This study analyzes the impact of savings, loan interest rates, property sector NPLs, and the number of housing loans before and after a LTV policy revision. The data analysis used the Paired t-test, Wilcoxon signed-rank test, and multiple linear regression. The study results showed that there were differences between savings, loan interest rates, property sector NPLs, and the number of mortgages before and after a LTV policy change. Savings and NPLs in the property sector have no impact on the demand for housing loans while loan interest rates and LTV policy significantly affect the demand for housing loans.